2011
DOI: 10.1007/s11095-011-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryogrinding on Chemical Stability of the Sparingly Water-Soluble Drug Furosemide

Abstract: Purpose To investigate the effect of cryogrinding on chemical stability of the diuretic agent furosemide and its mixtures with selected excipients. Methods Furosemide was ground at liquid nitrogen temperature for 30, 60, 120 and 180 min. Mixtures of furosemide-PVP and furosemide-inulin (1:1) were milled under cryogenic conditions. Materials were analyzed by XRD, UPLC, MS and NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 35 publications
2
60
0
1
Order By: Relevance
“…Milling can also impact the chemical stability. Cryomilling has been shown to amorphize furesomide [47] and also to induce some chemical degradation and appearance of impurities. Such chemical degradation can be linked to the modification of the structural relaxations and specificity of the sub-Tg molecular mobility revealed by our investigation.…”
Section: Conclusion Link With Physical and Chemical Stabilitymentioning
confidence: 99%
“…Milling can also impact the chemical stability. Cryomilling has been shown to amorphize furesomide [47] and also to induce some chemical degradation and appearance of impurities. Such chemical degradation can be linked to the modification of the structural relaxations and specificity of the sub-Tg molecular mobility revealed by our investigation.…”
Section: Conclusion Link With Physical and Chemical Stabilitymentioning
confidence: 99%
“…Milling is one the most common particle size reduction step. The effect of milling parameters, such as milling frequency, impact velocity, milling time on particle bulk and surface properties, is well documented in the literature Adrjanowicz et al, 2011;Forcino et al, 2010;Vegt et al, 2009;Shariare et al, 2011;Perkins et al, 2009;Kwan et al, 2004;Kwan et al, 2003;Leleux and Williams, 2014;Newman and Zografi, 2014). Kwan et al investigated the effect of milling frequency and propensity of breakage for microcrystalline cellulose and α-lactose monohydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Adrjanowicz et al demonstrated that milling at cryogenic temperature can result in chemical decomposition of furosemide. Chemical stability of furosemide was reported to be effected by the generation of the amorphous phase under cryogenic milling conditions (Adrjanowicz et al, 2011). A higher reactivity of the amorphous phase was linked to the acid catalysed hydrolysis of the amorphous phase of furosemide, resulting in undesirable chemical changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the solubility of API is expected to be improved via amorphization. However, physical and chemical stabilities remain still challenging in cryogenic co-grinding 13 , and consequently, the inclusion of a stabilizing carrier polymer or polymer mixture is essential.…”
Section: Introductionmentioning
confidence: 99%